Σύγκριση Μεθόδων Διπλών Διαφορών (ΔΔ) και Precise Point Positioning (PPP) Στην Επεξεργασία Μετρήσεων GPS - Μπίρης, Θωμάς (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών. Τομέας Τοπογραφίας. Εργαστήριο Ανώτερης Γεωδαισίας., 2014)
The current thesis regards the comparison between two methods of GPS data analysis. The first one is the traditional double difference method and the second one is the precise point positioning (PPP). The PPP method entails advantages, such as being less time consuming and less infrastructure demanding compared to the double difference method, but its accuracy and reliability has yet to be proven.